A case of transcatheter aortic valve implantation complication with total femoral artery thrombosis due to failure of the ProStar device - İsa Öner Yüksel; Erkan Koklu; Sakir Arslan; Goksel Cagirci; Selcuk Kucukseymen (Türk Kardiyoloji Derneği Arşivi, 2015)
Vascular complications in transfemoral transcatheter aortic valve implantation are relatively frequent and there is increased morbidity and mortality risk in the procedure. This report presents successful surgical repair of a femoral artery thrombosis case following an implantation procedure.